(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the open interventional management options and their outcome in patients suffering from fibroid uterus at tertiary care hospital Study Design: Cross Sectional study. Place and Duration of Study: This study was conducted at the Department of Gynae and Obstet Unit 2, PMC Hospital Nawabshah from January 2017 to December 2017. Materials and Methods: This study was conducted at Peoples Medical College Hospital Nawabshah. All the patients were admitted through Out Patient Department (OPD) and emergency department with history heavy menstrual bleeding lower back pain, pelvic pain, infertility, miscarriages and pain during intercourse etc. Thorough clinical examination along with required biochemical and radiological investigations were done. Diagnosis was made and treated accordingly. Results: This is one year study of total 50 patients. It included two groups of female patients. Group A included 15 (30%) patients aged between 20 to 35 years. Group B included 35 (70%) aged from 36 to 56 years. Group A patients underwent myomectomy and group B were operated for open trans abdominal Hysterectomy (open TAH). Conclusion: Myomectomy and trans abdominal hysterectomy are the better procedures in our study to cure the disease of uterine fibroids.